Gravitational Lensing and Optical Geometry: A Centennial Perspective (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The year 2019 saw the centenary of Eddington's eclipse expeditions and the corroboration of Einstein's general relativity by gravitational lensing. To mark the occasion, a Special Issue of Universe has been dedicated to the theoretical aspects of strong gravitational lensing. The articles assembled in this volume contain original research and reviews and apply a variety of mathematical techniques that have been developed to study this effect, both in 3-space and in spacetime. These include: · Mathematical properties of the standard thin lens approximation, in particular caustics; · Optical geometry, the Gauss–Bonnet method and related approaches; · Lensing in the spacetime of general relativity and modified theories; black hole shadows.